Penilaian dan Analisis Nilai Likuidasi Dump Trucks: Studi Kasus di Kota Cilegon, Banten - Novrizal, Aditya; Iqbal, Muhammad (Polytechnic of State Finance STAN, 2024)
This research aims to assess the fair market value and liquidation value of 35 trucks owned by a company in Cilegon City, Banten, which will be used as collateral for loans at financial institutions. The Market Data Approach with Comparable Match technique was employed. This method was chosen because the valuation object, the trucks, is a common asset in the market, making it relatively easy to obtain relevant comparative data. Through in-depth analysis of market data, vehicle physical condition, and relevant economic factors, the valuation results indicate that the fair market value of the trucks as of May 27, 2024, was Rp 13,465,400,000, while the liquidation value was lower at Rp 9,425,780,000. This difference reflects the liquidation discount that typically occurs in quick asset sales. The results are expected to provide valuable information for decision-making related to loan collateral and for asset owners to record the value of their assets.